Analisis Penggunaan Pias-Pias Kata dalam Meningkatkan Minat Membaca Siswa Kelas 1 Min 1 Probolinggo - Intan Permata Sari; Kustiana Arisanti; Nani Zahrotul Mufidah (Journal on Education, 2023)
In this modern era, almost every village, even the city, already has learning institution facilities, namely education. Education is needed to grow generations that are beneficial to the State and Religion. Beginning with a knowledge process in which a student is required to be able to read and understand the text. In this case the researcher used descriptive qualitative research. The purpose of reading is so that students can find news, information, and knowledge from the results of reading, with this reading is also carried out by several institutions, namely MIN 1 Probolinggo to educate the nation by learning to read. Interest in reading is part of the initial process for students to be able to open up a space of knowledge, experience and insight. In terms of learning the teacher uses word fragment media with letter fragments that make it easier for students to spell letters so as to produce words. This method is done so that students can read well quickly. All efforts made have obstacles, namely each student's different character and low student interest in reading. With this learning method, each student will definitely be able to read over time.